Crotonylation-Related Prognostic Model of Esophageal Squamous Cell Carcinoma Based on Transcriptome Analysis and Single-Cell Sequencing Analysis - Lin RY; Chen RP; Lin FQ (International Journal of General Medicine)
Ruo-Yang Lin,1 Ren-Pin Chen,1 Fu-Qiang Lin2 1Department of Gastroenterology and Hepatology, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, 325000, People’s Republic of China; 2Department of Thoracic Surgery, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, 325000, People’s Republic of ChinaCorrespondence: Fu-Qiang Lin, Email linfq66@qq.comBackground: Crotonylation is an emerging lysine acylation modification implicated in various diseases, yet its role in esophageal squamous cell cancer (ESCC) is unexplored. This study aimed to investigate the role of crotonylation-related genes (CRGs) in ESCC using bioinformatics approaches.Methods: We included three ESCC datasets and 24 CRGs. Differentially expressed genes (DEGs) from TCGA-ESCA were intersected with key module genes related to CRGs to identify candidate genes. Univariate and LASSO regression analyses were conducted to select prognostic genes, which were then used to construct risk models. Independent prognostic analysis and nomogram construction followed. Functional enrichment and immune infiltration analyses were performed using the prognostic genes. Single-cell analysis was conducted to assess cell communication and pseudotemporal dynamics in key cells.Results: Intersection of 1529 DEGs with 1,048 key module genes yielded 55 candidate genes. OSM, FABP3, MICB, and FAM189A2 were identified as prognostic genes. These genes were used to classify ESCA patients into different risk groups and construct a nomogram. FABP3 and FAM189A2 were enriched in neuroactive ligand-receptor interaction and ribosome terms. MICB and FABP3 showed strong positive correlations with natural killer T (NKT) cells, while FAM189A2 negatively correlated with gamma delta T (γδT) cells. Single-cell analysis identified mast cells and neutrophils as key cells, differentiating into seven and three states, respectively.Conclusion: Four genes (OSM, FABP3, MICB, and FAM189A2) were identified as prognostic crotonylation-related genes in ESCC, potentially involved in its pathogenesis. OSM was negatively correlated with ESCC, while FABP3 and MICB were positively correlated.Keywords: esophagus cancer, crotonylation, risk model, prognostic genes, single-cell sequencing analysis